2016
DOI: 10.1108/arj-08-2013-0055
|View full text |Cite
|
Sign up to set email alerts
|

The impact of IFRS 7 on the significance of financial instruments disclosure

Abstract: Purpose -The main aim of this paper is to investigate Financial Instrument (FI) disclosures provided by Jordanian listed companies under IFRS 7 as compared to those supplied under IAS 30/32.Design/methodology/approach -A sample of 82 Jordanian listed companies is used in this monograph. A disclosure index checklist was constructed to measure FI information provided by the sample companies.Findings -The study finds that a larger number of Jordanian listed companies provided a greater level of FI-related info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 64 publications
1
28
0
2
Order By: Relevance
“…For specific standards, the results may be even lower, e.g. 49% and 40% compliance with IFRS 7 requirements in Jordan 2007 (Tahat et al, 2016) and Malawi 2009 (Tauringana & Chithambo, 2016), respectively. The lower bound (poorest disclosers) are in many cases 10-20 percentage points below the average compliance level (46% is the average lower bound of the studies covered).…”
Section: Disclosure Compliance Levels -Empirical Results and Methodologymentioning
confidence: 96%
See 2 more Smart Citations
“…For specific standards, the results may be even lower, e.g. 49% and 40% compliance with IFRS 7 requirements in Jordan 2007 (Tahat et al, 2016) and Malawi 2009 (Tauringana & Chithambo, 2016), respectively. The lower bound (poorest disclosers) are in many cases 10-20 percentage points below the average compliance level (46% is the average lower bound of the studies covered).…”
Section: Disclosure Compliance Levels -Empirical Results and Methodologymentioning
confidence: 96%
“…The first group gathers studies dealing with the adoption of and compliance with IFRS (or national GAAP) disclosure requirements in Bahrain (Juhmani, 2017); Bangladesh (Akhtaruddin, 2005;Hasan, Karim, & Quayes, 2008); China (Gao & Kling, 2012;Peng, Tondkar, van der Laan Smith, & Harless, 2008;Xiao, 1999); Egypt (Abd-Elsalam & Weetman, 2003;Dahawy, Merino, & Conover, 2002;Hassan, Giorgioni, & Romilly, 2006;Hassan, Romilly, Giorgioni, & Power, 2009;Samaha & Abdallah, 2012); Ghana (Assenso-Okofo, Ali, & Ahmed, 2011); Jordan (Al-Akra, Eddie, & Ali, 2010); Kenya (Bova & Pereira, 2012); Malaysia (Abdullah, Evans, Fraser, & Tsalavoutas, 2015;Che Azmi & English, 2016); Saudi Arabia (Naser & Nuseibeh, 2003); Turkey (Çürük, 2009;Mısırlıoglu, Tucker, & Yükseltürk, 2013) and Zimbabwe (Chamisa, 2000). The second category includes studies of business combinations in China (Taplin, Zhao, & Brown 2014); financial instrument disclosures in Malaysia (Othman & Ameer, 2009), Egypt (Mokhtar & Mellett, 2013), Jordan (Tahat, Dunne, Fifield, & Power, 2016) and Malawi (Tauringana & Chithambo, 2016); presentation of financial statements (IAS 1) in Malaysia (Rahman & Hamdan 2017); income taxes in Egypt (Ebrahim & Fattah, 2015). The third category includes general disclosure compliance studies covering Bahrain, Oman, Kuwait, Saudi Arabia and United Arab Emirates (Al-Shammari, Brown, & Tarca, 2008); Bangladesh, India and Pakistan (Ali, Ahmed, & Henry, 2004); Malaysia, Philippines and Thailand (Taplin, Tower, & Hancock, 2002); 7 and one study of Islamic banks in Bahrain, Qatar, Jordan, Syria, Sudan, Yemen and Palestine …”
Section: Disclosure Compliance Levels -Empirical Results and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies by many authors, notably Li, Sougiannis, and Wang (2017), Chang, Donohoe, and Sougiannis (2016), Gumb, Dupuy, Baker, and Blum (2018), Schwarzbichler, Steiner, and Turnheim (2018), testify to information advantages of formation of financial statements under IFRS for the purposes of management of financial instruments on the basis of increase of prognostic value of reporting information. For example, research by Tahat, Dunne, Fifield, and Power (2016) on companies operating in Jordan showed that as a result of https://doi.org/10.15405/epsbs.2020.03.96 Corresponding Author: E. E. Popova Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 672 the application of IFRS in the preparation of financial statements, they have achieved a higher level of disclosure of financial activities, especially from the application of IFRS 7.…”
Section: Problem Statementmentioning
confidence: 99%
“…In terms of developing countries, empirical studies on FI disclosure are very scarce (Hassan et al, 2006a). Exceptions to this include some studies conducted in Malaysia (Hassan et al, 2006b), the Czech Republic (Strouhal, 2009), Brazil (Murcia and Santos, 2010) and Jordan (Tahat et al, 2016). The results revealed that although firms provided FI-related information, there was a great deal of variation in the information provided, as compared to the IASB's standards such as IAS 32, IAS 39 and IFRS 7.…”
Section: Empirical Evidence On Fi Disclosurementioning
confidence: 99%